Keanekaragaman Musuh Alami Koloni Lepidotrigona terminata Smith (Hymenoptera: Apidae: Meliponinae): Diversity of Natural Enemies in the Colony of Lepidotrigona terminata Smith (Hymenoptera: Apidae: Meliponinae) - Wicaksono, Anggun; Atmowidi, Tri; Priawandiputra, Windra (Departemen Biologi, Institut Pertanian Bogor, 2020)
The research about types of natural enemies of stinless bees Lepidotrigona terminata had been conducted in West Java. All natural enemis were identified morphologically and their habitat. There were 687 individuals of 14 species of natural enemies obtained in this research, i.e., Pseudeuophrys sp., Heliophanus sp., Argiope versicolor, Plexippus paykuli, Marpissa sp., Parasteatoda tepidariorum, Tegenaria sp., Nasutitermes javanicus, Paratrechina sp., Polyrhachis sp., Paratrechina longicornis, Rhynchium haemorrhoidale, Hemidactylus frenatus and Hemidactylus garnotii. Based on observation, spider, ants, and lizard were the predators of stingless bee. The results are expected as data and knowledge in the conservation and cultivation of stingless bees.